Through-silicon-via formation of 3D electronic modules by laser radiation - V. L. Lanin; V. T Pham; A. I. Lappo (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2021)
Laser  heating  is  a  promising  method  for  through-silicon-via  (TSV)  formation  in  assembling  highdensity 3D electronic modules due to its high specific energy and local heating ability. Using laser radiation for the formation of TSV makes it possible to reduce its diameter, indirectly increases the density of elements in 3D electrical  modules.  Laser  system  selection  depends  on  the  physical  and  mechanical  properties  of  the processed materials and on the technical requirements for laserprocessing. The reflectivity of most materials increases with the laser wavelength. It was found that with an increase in the initial temperature of the substrate, the  TSV  taper  becomes  larger.  Simulation  was  performed  in  COMSOL  Multiphysics 5.6  to  conduct  thermal distribution during TSV laser formation. By modeling thermal fields in the COMSOL Multiphysics 5.6 software for  laser  processing  of  silicon  substrates  and  experimental  studies,  the  parameters  of  laser  radiation  have been optimized  to  obtain  a  minimum  hole  taper  coefficient  in  the  substrates  of  3D  electronic  modules. The optimal  duration of  exposure  to  laser radiation  with a  wavelength of 10.64 microns  is  less  than  2 s with holes taper 0.1–0.2.